2019
DOI: 10.1038/s41598-019-50906-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed supplementation with biosynthesized silver nanoparticles using leaf extract of Morus indica L. V1 on Bombyx mori L. (Lepidoptera: Bombycidae)

Abstract: Herein, we report the synthesis of silver nanoparticles (AgNPs) by a green route using the aqueous leaf extract of Morus indica L. V1. The synthesized AgNPs exhibited maximum UV-Vis absorbance at 460 nm due to surface plasmon resonance. The average diameter (~54 nm) of AgNPs was measured from HR-TEM analysis. EDX spectra also supported the formation of AgNPs, and negative zeta potential value (−14 mV) suggested its stability. Moreover, a shift in the carbonyl stretching (from 1639 cm−1 to 1630 cm−1) was noted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 70 publications
7
57
0
Order By: Relevance
“…The peaks at 3300-3500 cm −1 reflect strong N-H stretching in alcohols as well as phenolic and flavonoid compounds. The peaks at 1627.73 cm −1 and 1635.44 cm −1 correspond to carbonyl stretching frequency, as reported by Some et al at 1630 cm −1 for AgNPs synthesized from Morus indica leaf extract [33]. The FTIR spectrum of AgNPs-and M. macroura leaf extract revealed strong interactions with the fruit extract during their synthesis.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)supporting
confidence: 68%
“…The peaks at 3300-3500 cm −1 reflect strong N-H stretching in alcohols as well as phenolic and flavonoid compounds. The peaks at 1627.73 cm −1 and 1635.44 cm −1 correspond to carbonyl stretching frequency, as reported by Some et al at 1630 cm −1 for AgNPs synthesized from Morus indica leaf extract [33]. The FTIR spectrum of AgNPs-and M. macroura leaf extract revealed strong interactions with the fruit extract during their synthesis.…”
Section: Fourier-transform Infrared Spectroscopy (Ftir)supporting
confidence: 68%
“…The -OH groups present in flavonoids are responsible for the reduction of nanoparticles. It has been proposed that hydrogen ions are released during the tautomeric transformation of the enol form of flavonoids to keto form, resulting in the reduction of metal ions and formation of metal nanoparticles [34]. In this study, the total phenolic content of Piper retrofractum extract was approximately about 0.98 mg GAE/g.…”
Section: Synthesis and Mechanism Of Cunps Formationmentioning
confidence: 65%
“…The extracts exhibited significant dose-dependent inhibition of growth on HT-29 cells with IC 50 values of 169.7 µg/ml (MV1ME) and 55.01 µg/ml (MV1A) respectively. Some S et al, (2019) 29 , reported maximum cytotoxicity of 41% and 49% by MV1 aqueous extract based silver nanoparticles at 250µg/ml concentration on HepG2 and WRL-68 human cancer cell lines respectively with a IC 50 higher than 250 µg/ml. In our study, the aqueous extract of MV1 showed high cytotoxic effect on colon cancer cell line with very low IC 50 value.…”
Section: In-vitro Cytotoxic Effect Of Morus Indica V1 In Ht-29 Cell Lmentioning
confidence: 99%